(3efXheI aj Yde GdWH GdYGes - (3CHh HcQ eMeO Hf YHO Gdedc GdbjSj, GHf GdWajd,J (B381 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdXGgQ Pi Gdedc hGdeLO GdbGgQI (B((3X(B) (3hChd GdefXheI (B: (3HGH ai OGA GdKYdH Ef dgPG GdOGA aGYde SHHG abO jchf fJ Oe bO ZdHG s
(3BNQgG (B:s
(3PQ YdjgG GdedM hGdQeGOG aEfg jSbWgG CHOG ced LejY GdOjhGf hGdMeO ddg s
(3JfbU HYV GdChQGb ef GdOGNds
(3QJHgG Ydi SHY ebGdGJ ai (B7700 (3HjJs
(3HChdgG JMHjS dCHi GdYHGS CMeO GdefUhQ GdSYOis
(3hai CYdi GdJMHjS NW UGMHI s
(3hGdfSNI ebGHdI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs